The Development of Interactive Flipbook-Formed Teaching Material to Improve the of Grade 4 Students’ Social Science Learning Outcomes - Solikhatun, Florentina Widihastrini, Rizky (Elementary School Teacher, 2018)
Social studies learning outcomes for some students have not yet reached the KKM (Minimum Score Criteria), this is influenced by the limited teaching materials and the use of less optimal learning media. This research was a type of development research. This study was aimed to develop flipbook teaching materials, to test the feasibility of flipbook, test materials and the effectiveness of flipbook as teaching materials.The subject of this research was the fourth grade students of SDN Kandri 01 Semarang city, Central Java. In this study, researchers used saturated sample technique with a total of 42 students. The Data was collected by observation techniques, interviews, questionnaires, tests and documentation. Researchers processed data using product data analysis, early data analysis, t test, and gain test. The results showed that the flipbook material was very feasible to use with the percentage expert material assessment of 87.5%, media experts of 87.5% and linguists 75%. Based on learning outcomes there was an average difference through the t test of 7,113 and the average increase of 0,349 with medium criterion. As conclusion, the flipbook teaching materials was very feasible and effective for helping the student to learn about IPS Subject